The Association of the MTHFR Gene Polymorphisms with Breast Cancer Susceptibility - Ahmad Hamta; Zahra Bozorgi Moghadam (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām, 2023)
Introduction: Breast cancer is the most common malignancy in women worldwide. It is also the second leading cause of cancer death among women after lung cancer. Considering the relationship among plasma folate levels, the level of uracil, and DNA damage in cell division, methyl tetrahydrofolate reductase (MTHFR) is a suitable candidate for studies on the susceptibility to cancer, including breast cancer. This study aimed to investigate the relationship between two polymorphisms in the MTHFR gene and the risk of breast cancer among women in Markazi Province, Iran. Material & Methods: This case-control study investigated the rs1801131 and rs1801133 polymorphisms of the MTHFR gene and breast cancer risk in a large population including 80 patients and 80 healthy women in Markazi Province, Iran, using the PCR-RFLP technique. The specimens were genotyped by agarose gel electrophoresis. Finally, the data were analyzed in SPSS software (version 26). (Ethic code: Ir.arakmu.rec.1396.25) Findings: There was a statistically significant difference between the two groups of patients and controls regarding three genotypes of the rs1801133 locus (P=0.006). Moreover, the CT genotype (P=0.001, OR=2.471, 95% CI=1.229-4.965) and total TT and CC genotypes (P=0.000, OR=3.375, 95% CI=1.716-6.637) were significantly associated with the risk of breast cancer. However, the TT genotype (P=0.538) showed a protective role against breast cancer. In contrast, there was no statistically significant difference between the two groups of patients and controls in terms of three genotypes of the rs1801131 locus (P=0.149), which is consistent with the results of some studies. Discussion & Conclusion: The rs1801133 polymorphism of the MTHFR gene can be used as a marker in clinical prognostic studies related to the risk of breast cancer.